Ultrasonic Powder Atomization for Additive Manufacturing - Halapi, David; Varga, László (International Journal of Engineering and Management Sciences, 2023)
The following article presents a special case of metal powder production, ultrasonic metal atomization. In this case, ultrasound technology is based on the capillary wave phenomenon. We verify the suitability of the produced powders for 3D metal printing with various tests. In the case of prints with a metal powder bed fusion (PBF), the properties of the raw material of the powder are extremely important. The main results of the tests carried out in the article (SEM images, EDS composition analysis, sieve analysis) were described.